Geological tasks during HI-SEAS planetary analog mission simulations, Mauna Loa, Hawai'i. (March 2022) - Shiro, Brian R.; Rowland, Scott K.; Hurtado, Jose M.; Caldwell, Bryan J.; Bleacher, Jacob E.; Fagents, Sarah A.; Roma, Peter G.; Bedwell-Torres, Wendy L.; Binsted, Kim
Abstract: The Hawai'i Space Exploration Analog and Simulation (HI-SEAS) project is a NASA-funded research program operating long-duration planetary analog surface mission simulations on Mauna Loa volcano, Hawai'i. During missions lasting from 4 to 12 months, crews of six analog astronaut participants live and work in an isolated habitat, communicating with a remote mission support team via a 20-min time delay. The main purpose of HI-SEAS is to study team effectiveness and adaptation over time in isolated, confined, and high autonomy mission scenarios. Among other duties, Crewmembers are tasked with routinely conducting geological fieldwork requiring extravehicular activity (EVA) in the environment surrounding the habitat. They must determine how they will accomplish these tasks, conduct the tasks themselves, and report results by a due date set by the remote science team. Here we describe the design, task parameters, and performance outcomes of HI-SEAS geology EVA tasks from four 6-person missions. We describe the assigned tasks, how the crews carried out their assignments, and the results of their work in terms of six performance metrics for each task: 1) number of days required for completion; 2) number of crewmembers participating; 3) number of EVAs required; 4) total EVA time required; 5) difference between required and planned EVA times; and 6) performance score evaluating how well crew met the task objective. We find weak evidence of a decrease in geology task performance during the third quarter of missions M2-M4. This dataset provides insights into varying crew performance over time for different mission durations. Highlights: Geologic field tasks were given to 6-person crews during 4 simulated long-duration planetary missions on Mauna Loa, Hawai'i. Crews performed tasks in extra-vehicular activities that they planned and executed, reporting results to the science team. Six metrics evaluating crew performance to study team effectiveness during isolated, confined, and high autonomy missions. Crew performance across missions showed sensitivity to differences between tasks, crews, and changes within crews over time. These tasks aid in investigating behavioral factors of operational performance in long-duration isolation and confinement.